Arsenic Binding and Transfer by the ArsD As(III) Metallochaperone - Yang, Jianbo (2010)
ArsD is a metallochaperone that delivers trivalent metalloids [As(III) or Sb(III)] to the ArsA ATPase, the catalytic subunit of the ArsAB pump encoded by the arsRDABC operon of Escherichia coli plasmid R773. Interaction with ArsD increases the affinity of ArsA for As(III), conferring resistance to environmental concentrations of arsenic. Previous genetic analysis suggested that ArsD residues Cys12, Cys13, and Cys18 are involved in the transfer of As(III) to ArsA. Here X-ray absorption spectroscopy was used to show that As(III) is coordinated with three sulfur atoms, consistent with the three cysteine residues forming the As(III) binding site. Two single-tryptophan derivatives of ArsD exhibited quenching of intrinsic protein fluorescence upon binding of As(III) or Sb(III), which allowed estimation of the rates of binding and affinities for metalloids. Substitution of Cys12, Cys13, or Cys18 decreased the affinity for As(III) more than 10-fold. Reduced glutathione greatly increased the rate of binding of As(III) to ArsD but did not affect binding of As(III) to ArsA. This suggests that in vivo cytosolic As(III) might be initially bound to GSH and transferred to ArsD and then to ArsAB, which pumps the metalloid out of the cell. The As(III) chelator dimercaptosuccinic acid did not block the transfer from ArsD to ArsA, consistent with channeling of the metalloid from one protein to the other, as opposed to release and rebinding of the metalloid. Finally, transfer of As(III) from ArsD to ArsA occurred in the presence of MgATP at 23 °C but not at 4 °C. Neither MgADP nor MgATP-γ-S could replace MgATP. These results suggest that transfer occurs with a conformation of ArsA that transiently forms during the catalytic cycle.